2011
DOI: 10.1063/1.3655817
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation strategies for computing the wetting properties of fluids at geometrically rough surfaces

Abstract: We introduce Monte Carlo simulation methods for determining the wetting properties of model systems at geometrically rough interfaces. The techniques described here enable one to calculate the macroscopic contact angle of a droplet that organizes in one of the three wetting states commonly observed for fluids at geometrically rough surfaces: the Cassie, Wenzel, and impregnation states. We adopt an interface potential approach in which the wetting properties of a system are related to the surface density depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 69 publications
2
47
0
Order By: Relevance
“…Dewetting in hydrophobic confinement can also be important in a host of nonbiological phenomena, ranging from heterogeneous nucleation of vapor bubbles and contact line pinning, to the Cassie-Wenzel transitions on textured surfaces (60). These phenomena involve intricate confinement geometries, which could result in complex pathways involving one or more transitions between various dewetted morphologies, akin to the transition between isolated cavities and vapor tubes observed here.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Dewetting in hydrophobic confinement can also be important in a host of nonbiological phenomena, ranging from heterogeneous nucleation of vapor bubbles and contact line pinning, to the Cassie-Wenzel transitions on textured surfaces (60). These phenomena involve intricate confinement geometries, which could result in complex pathways involving one or more transitions between various dewetted morphologies, akin to the transition between isolated cavities and vapor tubes observed here.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…As a result, most studies of adsorbed fluids resort to a plain truncation of fluid-fluid forces, without any attempt to correct for the missing interactions. [8][9][10][11][12][13][14][15][16][17][18] Already a while ago, Mansfield and Theodorou pointed out that truncating r −6 fluid-fluid interactions in systems where a z −3 fluid-wall potential is employed would have the effect of considerably favoring adhesive over cohesive interactions, and hence, very much affect the work of adhesion of adsorbed polymer films. 19,20 In order to remedy this problem, they developed a method for the calculation of tail corrections of adsorbed fluids.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Koshi et al [64] applied an external force to visit both the wetting states and calculated the work done during the transition between the two states. Kumar et al [68] also demonstrated a method to evaluate the free energies of different wetting states for the Lennard-Jones system using the grand canonical Monte Carlo (GCMC) simulation. Further, Leroy and Muller-Plathe [69] developed a phantom wall method to create a path between specific wetting states and that of a droplet on a smooth surface.…”
Section: Water Droplet On Textured Surfacesmentioning
confidence: 98%